Getting the NBN Infrastructure We Need - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2019)
This article summarises the presentation given to the author at the TelSoc NBN Futures event held in Melbourne on 31 July 2019.  The author spoke in favour of retaining NBN Co in public ownership, at least for the medium term and until a long term plan and evolution pathway has been established that will ensure that Australians have affordable access to world’s best broadband service and that delivers social and economic inclusion.  Dr Holmes argued that there were positive reasons supporting public ownership, and also that it was the least worst of the options available.